Program of the 20th annual research day: scientific proceedings - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, author (Colorado State University. Libraries, 2019)
Our 20th Annual Research Day showcases the work of more than 100 aspiring scientists in Colorado State University's College of Veterinary Medicine and Biomedical Sciences. The event gives our rising stars vital experience presenting their research findings to a scientific audience through poster displays and talks. The day also provides young researchers with an avenue for feedback to help them develop ideas that, in many cases, will become lifelong scientific pursuits. The research projects on display are sponsored by companies, foundations, and institutions concerned with improving human, animal, and environmental well-being. Thank you for supporting and engaging with our presenters – undergraduate students, graduate students, veterinary residents, and postdoctoral fellows – as they pursue research that will improve the health of animals, people, and the planet!

Includes the Zoetis Research Excellence Award winner, program of oral sessions and poster presentations.
20th annual CVMBS research day program
Colorado State University, College of Veterinary Medicine and Biomedical Sciences, 20th annual CVMBS research day scientific proceedings, program
Held on January 26, 2019 at the C. Wayne McIlwraith Translational Medicine Institute.
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses